Linguistic Ecology of Makassar's Green Spaces: Navigating Environmental Awareness through Language - Asnur, Sardian Maharani; Djamaluddin, Junardin (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2024)
This research investigates the linguistic ecology of Makassar’s green spaces and its role in navigating environmental awareness through language. Focusing on popular landmarks in Makassar City, including Losari Beach, Fort Rotterdam, Taman Macan and Lapangan Karebosi, the study examines the language used in signage (signs and information boards) plays related to environmental conservation and green space management. Through a combination of linguistics analysis and qualitative research method, this research comprises documentation and survey in gathering data. There are 60 respondents contribute in the survey (visitors, residents who live around the public green spaces, stakeholders, and groups of community). The findings identify that there are prevalent language patterns used in signage related to environmental awareness and green space management in Makassar’s popular landmarks; language influences people perception, attitudes, and behavior towards environmental conservation and sustainability practices in Makassar’s green spaces through several mechanism including narratives and framing, cultural relevance, accessibility and inclusivity, targeted communication, education and awareness, as well as social norms and peer influence. In conclusion, this research contribute to the understanding of the intricate relationship between language, environment, and society, with implications for environmental education, communication strategies, and policy interventions aimed at fostering greater environmental consciousness in urban setting like Makassar.Keywords: Linguistics Ecology, Environmental Awareness, Urban Sustainability, Green Spaces, Makassar City.